Do pre-surgery eating habits affect weight loss one year following a sleeve gastrectomy?. (June 2017) - Susmallian, Sergio; Raziel, Asnat; Nikiforova, Ilana; Sherf-Dagan, Shiri; Hershkovitz-Rokah, Oshrat; Barnea, Royi
Summary: Background: The laparoscopic sleeve gastrectomy (LSG) is one of the leading types of bariatric surgery. Surgeons commonly choose this procedure according to the patient's eating habits; however, this doctrine has not yet been reliably verified. Purpose: This study aimed to explore the effects of different eating habits prior to surgery on the success of an LSG. Methods: We conducted a cohort, observational, retrospective study at a private medical center. This research included 300 patients who underwent LSGs at a private Medical Center between 2013 and 2014. They were divided into groups according to their preoperative eating habits by the nutritionist on the bariatric committee, and the one year post-surgery body weight data was obtained from the medical records from our clinic. Results: The mean excess weight loss was 77%, with no significant difference between the groups one year after undergoing the LSG. The body mass index among the patients, regardless of their pre-operation eating habits, showed a reduction of 14.25 kg/m 2 one year after the LSG. The younger patients had significantly greater excess weight loss than those patients older than 50 years (81.13% vs. 72.44% and 14.95 kg/m 2 vs. 11.73 kg/m 2, respectively; p < 0.001). Conclusions: Our results suggested that preoperative eating habits do not impact the short-term success of an LSG. We are convinced that the long-term success of bariatric operations should be based on multidisciplinary support to encourage patients to maintain healthy eating habits. The study was registered in the National Institutes of Health web site with (ClinicalTrials.gov ) the study identifier NCT02733562.